IGF2BP2 gene polymorphism in patients with psoriasis. - Kargun, Kursat; Demir, Betul; Cicek, Demet; Kara, Murat; Bilik, Leyla; Kaya, Haktan (Allied Acad, 2017)
Psoriasis is a chronic inflammatory disease with genetic transmission, the etiology of which has not been completely clarified yet. Insulin-like Growth Factor Binding Protein 2 (IGF2BP2) plays a role in growth, development, cellular differentiation, and cellular metabolism, and IGF2BP2 gene exists on the 3rd chromosome. In the present study, we aimed to investigate the rs1470579 and rs4402960 gene polymorphisms of IGF2BP2 in patients with psoriasis, which were confirmed to be related with insulin resistance. The study was conducted with a total of 100 patients diagnosed with psoriasis who were between the ages of 18 to 60 years and 100 healthy volunteers as controls. Blood samples of the participants were isolated and Deoxyribonucleic Acid (DNA) samples were obtained and analysed using y the real-time Polymerase Chain Reaction (PCR) method with TaqMan probes for rs1470579 and rs4402960 polymorphisms. There was no statistically significant difference in the genotype and allele distributions of the rs1470579 and rs4402960 regions of IGF2BP2 between the groups (p>0.05). However, there was a statistically significant difference in triglyceride and Low-Density Lipoprotein (LDL) levels between the groups (p<0.001). rs1470579 and rs4402960 gene polymorphisms of IGF2BP2, which are considered to play a role in the course of type 2 diabetes mellitus, were not determined to be risk factors for the pathogenesis of psoriasis.
Keywords: Psoriasis; IGF2BP2; polymorphism; Real time PCR